2007
DOI: 10.1038/nm1654
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of FcεRI-mediated mast cell responses by ES-62, a product of parasitic filarial nematodes

Abstract: Atopic allergy is characterized by an increase in IgE antibodies that signal through the high-affinity Fcepsilon receptor (FcepsilonRI) to induce the release of inflammatory mediators from mast cells. For unknown reasons, the prevalence of allergic diseases has recently increased steeply in the developed world. However, this increase has not been mirrored in developing countries, even though IgE concentrations are often greatly elevated in individuals from these countries, owing to nonspecific IgE induction by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
195
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(215 citation statements)
references
References 28 publications
11
195
2
2
Order By: Relevance
“…In Vitro Assays. Human mast cells were derived from CD34 ϩ hematopoietic progenitor cells isolated from umbilical cord blood and cultured as previously described (26,34). Murine mast cells were isolated from the peritoneal cavity and cultured as previously described (35).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Vitro Assays. Human mast cells were derived from CD34 ϩ hematopoietic progenitor cells isolated from umbilical cord blood and cultured as previously described (26,34). Murine mast cells were isolated from the peritoneal cavity and cultured as previously described (35).…”
Section: Methodsmentioning
confidence: 99%
“…Similar results were observed for murine mast cells (data not shown). We have previously shown that at least two different pathways are used by antigen and cytokine receptors to trigger cytosolic calcium signals: the classical pathway that activates phospholipase C to generate IP 3 (22,23), and a novel pathway dependent on the activation of phospholipase D (PLD) and sphingosine kinase (SphK) (24)(25)(26). IL-33 triggered the activation and translocation of PLD1 (Fig.…”
Section: Molecular Mechanisms For Il-33 Triggered Mast Cell Degranulamentioning
confidence: 99%
“…Among others, a phosphatidylserine with specific chain length expressed by S. mansoni eggs engages TLR2 expressed on dendritic cells, which in turn induces IL-10-producing regulatory T cells (53). A secreted glycoprotein of the filarial nematode A. viteae inhibited Fc RImediated mast cell responses by forming a complex with TLR4, which resulted in the sequestration of protein kinase C-␣, a molecule important for mast cell activation (54,55). We provide evidence that cystatin protects from inflammation in a systemic fashion, as reflected by its effects on remarkably different compartments, such as the lung and the gut.…”
Section: Discussionmentioning
confidence: 84%
“…Human mast cells were derived from CD34 + hematopoietic progenitor cells isolated from umbilical cord blood and cultured as described previously (13,14). Mast cells were stimulated with TNF-a (10 ng/ml), IgG complexes (100 ng/ml), C5a (5 ng/ml), or LPS (10 ng/ml) for 24 h, and supernatant was tested for IL-1b, IL-5, IL-6, and IL-17A by ELISA (ELISA kits from eBioscience, Hatfield, U.K.).…”
Section: Mast Cell Stimulationmentioning
confidence: 99%